Time-dependent Radiation Transport Simulations of Infrared Echoes from Dust-shrouded Luminous Transients - Semih Tuna; Brian D. Metzger; Yan-Fei Jiang; Christopher White (The Astrophysical Journal)
A range of stellar explosions, including supernovae (SNe), tidal disruption events (TDE), and fast blue optical transients (FBOTs), can occur in dusty environments initially opaque to transients’ optical/UV light, becoming visible only once the dust is destroyed by transients’ rising luminosity. We present axisymmetric, time-dependent radiation transport simulations of dust-shrouded transients with Athena++ and tabulated gray opacities, predicting the light curves of the dust-reprocessed infrared (IR) radiation. The luminosity and timescale of the IR light curve depend on whether the transient rises rapidly or slowly compared to the light-crossing time of the photosphere, t _lc . For slow-rising transients ( t _rise  ≫  t _lc ) like SNe, the reprocessed IR radiation diffuses outward through the dust shell faster than the shell sublimates; the IR light curve therefore begins rising prior to the escape of UV/optical light, but peaks on a timescale ∼ t _rise shorter than the transient duration. By contrast, for fast-rising transients ( t _rise  ≪  t _lc ) such as FBOTs and some TDEs, the finite light-travel time results in the reprocessed radiation arriving as an “echo” lasting much longer than the transient itself. We explore the effects of the system geometry by considering a torus-shaped distribution of dust. The IR light curves seen by observers in the equatorial plane of the torus resemble those for a spherical dust shell, while polar observers see faster-rising, brighter, and shorter-lived emission. We successfully model the IR excess seen in AT2018cow as a dust echo, supporting the presence of an opaque dusty medium surrounding FBOTs prior to explosion.